2019
DOI: 10.1680/jgeot.18.p.104
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of soil arching in piled embankments

Abstract: The transfer of embankment stresses towards pile heads in piled embankments is attributed to the mechanism known as soil arching. Three-dimensional physical models of piled embankments were built to simulate this mechanism. The progressive settlement of subsoil beneath an embankment was modelled and paused at increments of displacements to allow synchrotron X-ray computed tomography to be performed on the models. Image correlation techniques were then applied to the reconstructed volumes to obtain evolving thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 49 publications
6
32
0
Order By: Relevance
“…However, the progressive development of the arching mechanism was not the focus of either study. Badakhshan et al (2020) were able to demonstrate reasonable agreement to the experimental study reported by King et al (2019b). However, their work did not expand the understanding of soil arching, and the load-displacement curve presented was not verified against experimental data.…”
Section: R a F Tmentioning
confidence: 76%
See 4 more Smart Citations
“…However, the progressive development of the arching mechanism was not the focus of either study. Badakhshan et al (2020) were able to demonstrate reasonable agreement to the experimental study reported by King et al (2019b). However, their work did not expand the understanding of soil arching, and the load-displacement curve presented was not verified against experimental data.…”
Section: R a F Tmentioning
confidence: 76%
“…The nature of the shear bands observed was akin to an inverted general bearing failure (Figure 3). This analogy assisted King et al (2019b) in explaining the four phases of soil arching behaviour described by Iglesia et al (1999):…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations